KONTRIBUSI MOTIVASI BELAJAR, PERILAKU PROSOSIAL DALAM IPS, DAN LINGKUNGAN KELUARGA TERHADAP PENGUATAN MODAL SOSIAL PESERTA DIDIK - Rohana, Tatang Rohana (JURNAL PENDIDIKAN ILMU SOSIAL, 2016)
This research is motivated by the increasing number of social deviation in the community that directly or indirectly affect the characteristics of learners. As a result, what the students see, experience and feel, also gives effect to the psychological and social development of learners, both positive and negative influences. Therefore, the necessary social capital of each learner as a result of learning social studies in school. The survey research was conducted in ten junior high schools in Subang with a sample of 360 eighth grade students were then divided proportionally. Data collection technique used observation, questionnaires, interviews, and literature studies. Data obtained from respondents, further processed and analyzed using path analysis (path analysis), the results are as follows: 1) learning motivation positive effect on social capital learners, 2) prosocial behavior in IPS positive effect on social capital learners, 3 ) family environment has a positive effect on social capital learners, 4) motivation to learn, prosocial behavior and the family environment, positive effect on social capital learners, 5) there is a significant difference between learning motivation, prosocial behavior, family environment and social capital learners based cluster region.Keywords: motivation to learn, prosocial behavior, family environment and social capital.